Relationship between Blood Pressure and Passive Smoking in Elementary School Children - Seyedzadeh, Abolhassan (Tehran University of Medical Sciences, 2012)
OBJECTIVE: Many diseases form their basis during childhood. One example is the changes in vascular structure and function, leading to atherosclerosis. In this study, we have assessed the impact of exposure to cigarette smoke on blood pressure of elementary school children in Kermanshah. METHODS: 80 elementary school children exposed to cigarette smoke and 80 not exposed to smoke were studied in fall 2010. Information regarding the smoking status of parents and the children’s health were obtained through questionnaires completed by parents. After physical examination and exclusion of those children with acute and chronic diseases as well as those consuming medicine, we measured and compared blood pressure in the exposure and non-exposure groups. Data were analyzed using the ANOVA statistical test. Values are expresses as Mean±SD. FINDINGS: The mean systolic and diastolic blood pressures of the exposure group were higher than those of the non-exposure group (109.3±9.97/64.92±7.36 vs105.47±8.98/62.5±7.01, respectively; CI: 0.95, P<0.05). Meanwhile, difference between two groups according to sex was not statistically significant. CONCLUSION: Our study indicates that systolic and diastolic blood pressures are higher in those elementary school children exposed to cigarette smoke compared to those who are not.